2014
DOI: 10.1002/ejic.201402689
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Search for an Iron‐Based Magnetic Superhalogen with Halogen or Interhalogen as Ligand

Abstract: By using density functional theory, we have investigated the geometrical structures, electrophilic properties, magnetic properties, and fragmentation channels of FeXn (X = Cl, Br; n = 1–6) clusters as well as the “mixed species” that contain interhalogen compounds. Our main objectives are to design new iron‐based magnetic superhalogens and to explore whether the interhalogen compounds are suitable for the superhalogen ligand. By calculating their adiabatic electron affinities (AEAs) and vertical detachment ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…They found that the Fe 2 Cl 5 + possesses the stronger magnetic coupling, and the degree of spin delocalization is larger than that in Mn 2 Cl 5 − . Inspired by these results, we have performed investigations on iron-based magnetic superhalogens with halogen (F, Cl, and Br) 30 or interhalogen (ClF, ClF 3 , ClF 5 , BrF, BrF 3 , BrF 5 , and BrCl) 31 as ligand. However, most of the previous works of magnetic superhalogens are concentrated on halogen atoms as ligand.…”
mentioning
confidence: 99%
“…They found that the Fe 2 Cl 5 + possesses the stronger magnetic coupling, and the degree of spin delocalization is larger than that in Mn 2 Cl 5 − . Inspired by these results, we have performed investigations on iron-based magnetic superhalogens with halogen (F, Cl, and Br) 30 or interhalogen (ClF, ClF 3 , ClF 5 , BrF, BrF 3 , BrF 5 , and BrCl) 31 as ligand. However, most of the previous works of magnetic superhalogens are concentrated on halogen atoms as ligand.…”
mentioning
confidence: 99%